Liwa Erbil Health Situation in Hashemite Monarchy Era (1921-1958) - Burhan Hatam Othman; Fatah Bahram khdir (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The health situation of each areas and city for each specific time of its history could be a criterion to know how health development of this area was. Erbil Liwa during Royal era was very bad situation. Lack of health service and spreading terrifying diseases were among the conspicuous figure of this era. This research consists of tow axes, first axes spotlight on Medical establishments, doctors, and nurses. In this axe also deals state and number of hospitals, medical centers, pharmacies, Doctors, nurses by comparing other Iraqi Liwa. The third axes mention the common diseases in Erbil Liwa of this era.